Nicaragua : 2017 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights Nicaragua's robust macroeconomic performance in 2016. Real GDP grew by 4.7 percent in 2016, supported by strong domestic demand, while inflation remained subdued at 3.1 percent as of the end of 2016, owing largely to the contribution of food prices. The current account deficit for 2016 is estimated to have narrowed to 8.6 percent of GDP, compared with 9 percent in 2015. This consolidation is largely explained by maquila exports, which have been better captured owing to improvements in statistical compilation. The current account deficit remained financed by foreign direct investment and other long-term inflows.